Is mathematical literacy detrimental to black youth employment? - SITHOLE, Gabisile (KDI School, 2016)
Youth unemployment, particularly among the Black youth in the age cohort, 15 to 24 years, is relatively high compared to their White, Coloured and India/Asian counterparts in the Gauteng province. The study investigates whether the subject, Mathematics Literacy (Maths Literacy), undermines the Black youth’s employment prospects. The study aims to highlight that the youth’s choice to study Maths Literacy over Core Mathematics (Maths) places them at a disadvantage when seeking decent employment and or to get admitted into key courses at university. The study uses data that was collected using the two questionnaires, which were intended to gain the Black youth’s high school subject choices and grades, perceptions and employers recruiting requirements. A logit regression is applied to analyse and illustrate that for every one unit change in the Black youth’s grade in Maths Literacy, the log odds of unemployment increase by 1.379. Indeed, supporting the objective of the study that Maths Literacy undermines the Black youth’s employment prospects, therefore contributing to rising youth unemployment.
Thesis(Master) --KDI School:Master of Development Policy,2016